Effectiveness of after-school interventions at increasing moderate-to-vigorous physical activity levels in 5- to 18-year olds: a systematic review and meta-analysis. Issue 21 (24th May 2016) - Mears, Ruth; Jago, Russell
Abstract : Aim: Physical activity in children improves cardiovascular, mental, metabolic and skeletal health. Many children fail to meet the national recommendation of at least 60 min per day of moderate-to-vigorous physical activity (MVPA). After-school programmes provide an opportunity to engage children in physical activity. This systematic review and meta-analysis examine the effectiveness of after-school interventions at increasing MVPA levels in children and adolescents. Design: Systematic review and meta-analyses. Data sources: A literature search was conducted using MEDLINE, EMBASE and PsychINFO databases from January 1950 to April 2015. Eligibility criteria for selecting studies: Inclusion criteria—Population: participants aged 5–18 years. Intervention: an after-school programme in a school-based setting as the main component of an intervention to increase physical activity levels. Outcomes: individual-level measure of time spent in MVPA. Study design: quasi-experimental, pilot, non-randomised or randomised trials. Exclusion criteria: conference abstracts, unpublished articles, dissertations and non-English language papers. Results: 1387 records were identified through database searching. After removal of duplicates, there were 748 records. 15 articles met the inclusion criteria for the systematic review. 6 studies were eligible for meta-analysis and the pooled intervention effect at end point follow-up was 4.84 min/day of MVPA (95% CI −0.94 to 10.61). The effectiveness of after-school interventions varied considerably and comparisons between studies limited by different methodological study designs. Subgroup analyses within a small minority of studies revealed significant benefits in overweight/obese children and boys. There was a lack of convincing evidence that interventions based on theories of behaviour change were more effective than those with no underlying theory. Conclusions: After-school physical activity interventions to date have had mixed effectiveness on increasing MVPA levels. More robust evaluations of extracurricular physical activity interventions are required, particularly studies that use objective assessment of physical activity.